District‐level impacts of health system decentralization in Indonesia: A systematic review. (22nd March 2019) - Rakmawati, Trisya; Hinchcliff, Reece; Pardosi, Jerico Franciscus
Summary: The local‐level impacts of decentralizing national health systems are significant yet infrequently examined. This review aims to assess whether localized health services delivery in Indonesia, which commenced a health system decentralization process in 2001, achieved its objectives or could be enhanced. A systematic review was undertaken to collate published evidence regarding this topic and synthesize key findings holistically using the six building blocks framework of the World Health Organization (WHO) to categorize health system performance. Four research databases were searched in 2016 for relevant evidence published between 2001 and 2015. The inclusion criteria were relevance to the topic of decentralization impacts at the district level, original research, and published in English. Included articles were appraised for quality using a standardized tool, with key findings synthesized using the WHO building blocks. Twenty‐nine articles met the inclusion criteria and categorized under the WHO building blocks categories. The findings highlight problematic impacts of decentralization related to three building blocks: service delivery, health financing, and workforce. In the 15 years of post‐decentralization in Indonesia, the service delivery, health workforce, and health financing blocks should be prioritized for further research and policy evaluation to improve the overall health system performance at the district level.